Humans-with-media and continuing education for mathematics teachers in online environments - Borba, Marcelo C. [UNESP] (Springer Nature, 2012)
This paper begins by situating online mathematics education in Brazil within the context of research on digital technology over the past 25 years. I argue that Brazilian research on technology in mathematics education can be divided into four phases, and then present an example that ‘‘blends’’ aspects of the second and third phases. Phase two can be characterized by research with software designed to address traditional mathematics topics, such as functions, while the third phase is characterized by online courses. The data presented show creative solutions for a problem designed for collectives of humans-with-function-software. The paper is analyzed from a perspective that emphasizes the role of different technologies as teachers and professors collaborate to produce knowledge about the use of mathematical software in regular face-to-face classrooms. A model of online education is presented. Finally, the paper discusses how technology may change collaboration and teaching approaches in continuing education, as it allows for greater integration of online learning with teachers’ classroom activities in schools. In this case, the online platform plays an active role in the learning collective composed of humanswith- media.
Keywords: Digital technology; Human–computer interaction; Mathematics education; Online teacher education